Correlation of blood glucose variability with peripheral neuropathy risk in type 2 diabetes patients: a cross-sectional analytical study - Rusli Rusli; Maria Kurni Menga; Rita Erlina; Nurlina Nurlina; Sara Palander (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Blood glucose variability (GV) has emerged as a potential determinant of microvascular complications beyond traditional glycemic markers such as HbA1c. However, evidence regarding its association with diabetic peripheral neuropathy (DPN), particularly in resource-limited settings, remains limited. This study aimed to analyze the correlation between GV and the risk of peripheral neuropathy among patients with type 2 diabetes mellitus (T2DM). Research Methodology: An analytical cross-sectional study was conducted among 85 patients with T2DM attending primary healthcare facilities in Makassar, Indonesia. Blood glucose variability was assessed using the coefficient of variation (CV), while peripheral neuropathy was evaluated using the Michigan Neuropathy Screening Instrument (MNSI). Bivariate analysis was performed using chi-square and correlation tests, followed by multivariable logistic regression to determine independent associations. Statistical significance was set at α = 0.05. Results: High GV (CV ≥36%) was significantly associated with peripheral neuropathy in bivariate analysis (OR = 3.46; 95% CI: 1.39–8.59; p = 0.007). In multivariate analysis, GV remained an independent predictor (adjusted OR = 2.98; 95% CI: 1.12–7.91; p = 0.028), whereas HbA1c ≥7% was not statistically significant (AOR = 2.67; 95% CI: 0.92–7.73; p = 0.071). Duration of diabetes showed a positive but non-significant association (AOR = 2.41; 95% CI: 0.89–6.54; p = 0.082). Conclusion: Blood glucose variability is an independent and clinically relevant predictor of peripheral neuropathy in T2DM patients. These findings support integrating GV assessment into routine diabetes management and highlight the need for strategies to improve glycemic stability and reduce the risk of complications.